2017
DOI: 10.1002/adsc.201700117
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Halogenation/Esterification of Alkenes with N‐Halosuccinimide and Acetic Acid Catalyzed by 1,4‐Diazabicyclo[2.2.2]octane

Abstract: Abstract1,4‐Diazabicyclo[2.2.2]octane (DABCO) is a suitable Lewis base that acts as an organocatalyst in the activation of N‐chlorosuccinimide (NCS) towards the chlorination of alkenes. The chloriranium ion formed from NCS and the alkene, can be intermolecularly opened by a nucleophile, such as acetic acid, to produce highly functionalized trans‐chloro esters in high yields. The protocol is also applied to the synthesis of chlorohydrins and chloro ethers using water or methanol as nucleophiles instead of aceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In case of ( S )‐citronellal (entry 10), we initially encountered a significant drop in the yield. Analysis of side products revealed that the trisubstituted alkene readily reacts with the more electrophilic Cl + source NO 2 NCP ( 19 ) compared to NCS ( 3 ) . As a major side product, we were able to isolate the allylic chloride of α‐chlorinated citronellal.…”
Section: Figurementioning
confidence: 99%
“…In case of ( S )‐citronellal (entry 10), we initially encountered a significant drop in the yield. Analysis of side products revealed that the trisubstituted alkene readily reacts with the more electrophilic Cl + source NO 2 NCP ( 19 ) compared to NCS ( 3 ) . As a major side product, we were able to isolate the allylic chloride of α‐chlorinated citronellal.…”
Section: Figurementioning
confidence: 99%
“…A known strategy to facilitate chlorination of organic substrates is the activation of N ‐chloroimides by Lewis bases . In one of our group's previous reports, we disclosed the activation of NCS with 20 mol% of 1,4‐diazabicyclo[2.2.2]octane (DABCO) to chlorinate 1‐octene . In the present study however, the use of DABCO as a catalyst was ineffective, delivering essentially the same result of the blank reaction (Entries 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of side products revealed that the trisubstituted alkene readily reacts with the more electrophilic Cl + source NO 2 NCP (19)c ompared to NCS (3). [21] As am ajor side product, we were able to isolate the allylic chloride of a-chlorinated citronellal. As only small amounts of (more reactive) enamine compared to the alkene are present in the reaction mixture,w ea imed to suppress undesired allylic chlorination by slow addition of the chlorinating agent.…”
mentioning
confidence: 99%